Technical Reference Framework for the Interoperability of Electronic Medical Record: Conceptual Model - Morales Rocha, Victor Manuel (2020)
This paper presents the domain modeling of a technical framework of sharing and interaction of an electronic me-dical record among different healthcare institutions, both public or private, as a first step to establish a technical reference framework for the interoperability of electronic medical record systems in Mexico. The artefact that make up the domain model were carried out using the KMOS-RE systematic process. Through this process, the following components have been obtained: the knowledge domain extended lexicon, the conceptual models, one for the application domain and another for the solution domain, as well as the state models. Since the design and imple-mentation of the electronic medical record systems of different healthcare institutions are generated independent-ly, having a technical reference framework represents a great challenge but also a great opportunity, since it will offer important advantages, such as having the clinical information in a timely manner in any healthcare institu-tion, the possibility of the patient accessing their own information and the ease of conducting clinical research from the shared data. Even when a domain modeling is a dynamic task, having a precise domain model at this point will facilitate the next steps to achieve the proposed technical reference framework.